Diseño de un plan de gestión integrada del manejo de residuos sólidos en minera aurífera Retamas S.A. Pataz - La Libertad - Mantari Camarena, Alcides Edgar (2012)
The mining industry is an one more complex belonging to them, considering that the raw materials that enter its process are of ample diversity, therefore the residues that come out of this also are it. The handling of his residues would not be possible, according to the normative present-day frame, if not lean of instruments of step like Integral's Plan of Manejo of Residuos Solid ( PIMRS ), which contains strategies, actions, objectives, resources and chronograms that they do that an organization be efficient and environmentally responsible. The PIMRS is a tool of indispensable step for the organizations, because it allows ordering and projecting his activities, of form such that the adverse impacts decrease to the environment, resources optimize themselves, gets a healthier environment and a better cohabitation with the communities of the surroundings. Present it investigation consists of 02 phases: The first constitutes the diagnosis and characterization of the residues, second phase is constituted for the strategies to execute m in each of the stages of the handling of solid residues in order to guarantee the optimal handling of the solid residues.